Developing a client-centred abortion counselling training course for healthcare providers - Kalyanaraman, Yamini (https://orcid.org/0000-0002-5993-7362) (Rhodes University, 2026)
The Choice on Termination of Pregnancy (CTOP) Act was passed in South Africa in 1996, drawing from both a public health and rights-based framework. Globally one of the more liberal pieces of legislation, the Act entrenched a woman’s right to early, safe and legal abortion, while promoting the provision of non-mandatory and non-directive counselling, both pre- and post-abortion. In 2008, an amendment to the Act allowed for trained registered nurses to provide abortions in order to increase accessibility. Despite this, research indicates that the current rate of illegal abortions remains high, at almost 50%. Almost three decades later, there are still hurdles to implementation and access. Baseline research conducted by the Critical Studies in Sexualities and Reproduction (CSSR) research unit at Rhodes University shows that pre-abortion counselling provided in public abortion clinics in the Eastern Cape province tends to be directive, with abortion seekers often being coerced into changing their minds and taking up, in particular, long-acting reversible contraception. This is a serious hindrance to reproductive rights, reproductive autonomy and quality reproductive healthcare, since fear of provider judgement may result in those who are pregnant resorting to illegal abortions out of fear, shame or both. My research aimed to develop, conduct, document and improve an abortion counselling training course for in-service nurses. This study operationalised the Abortion Counselling Guideline (published by the CSSR as part of the baseline study mentioned above) into a training course titled the Abortion Counselling Certificate Course (ACCC). Action Research methodology was adopted for curriculum design, course facilitation, evaluation, critical reflection, and refinement. The training course was conducted in partnership with the Eastern Cape Department of Health as a key stakeholder, and accredited as a short course by Rhodes University. The Abortion Counselling Certificate Course (ACCC) aimed to: build nurses’ skills in abortion counselling; promote client-centred and contextually relevant counselling based on reproductive justice principles; and dispel myths regarding abortion consequences with evidence-based research, ultimately benefiting the clients who access the service. Two training courses were conducted with nine nurse participants in each course. The first took place online (via Zoom) in 2020 during the COVID lockdown; the second took place face-to-face in 2021 at Rhodes University. Research data included feedback forms by the nurse participants, reflective journals maintained by the participants and me, recordings of selected sessions of the training course, participants' case presentations, and interviews with nurse participants two months after attending the first course. Data were analysed using a reflexive thematic analysis. The study was guided by the following questions: how did the reported learnings and reflections of the course participants dovetail with the specific outcomes of the training course; and what elements, whether internal or external to the course, were identified as enabling or hindering nurses’ skills in providing abortion counselling services based on reproductive justice principles. Findings show that several course outcomes were met, as the nurse participants demonstrated the following: enhanced critical thinking skills; deep listening by being attuned to clients’ verbal and non-verbal cues; use of evidence-based and non-stigmatising language; and an ability to be reflexive. A concern, however, is the maintenance of these newly acquired skills against a backdrop of staff shortages, infrastructural and resource constraints, lack of managerial support, and abortion stigma; these need to be further explored and overcome. This study makes a strong argument for a feminist, client-centred approach to abortion counselling grounded in reproductive justice principles. The course feedback was positive, with participants stating that the course enabled them to realise their own value and acquire self-respect as providers, to advocate for their clients, and to form peer support groups that assist with debriefing and sharing resources. Many said that the Rhodes University course certificate was the first formal acknowledgement they had received in all their years of service as abortion providers.
an action research project
Keywords: Abortion counseling (http://id.loc.gov/authorities/subjects/sh85000209); Nurses -- Training of (http://id.loc.gov/authorities/subjects/sh85093349); Client-centered psychotherapy (http://id.loc.gov/authorities/subjects/sh85027022); Pscyhology; Reproductive justice (https://www.wikidata.org/wiki/Q7314313)